Assessing Bank Stability in Malaysia in the Framework of Distance to Default - Asish Saha; Nor Hayati Ahmad; Lim Hock Eam; Siew Goh Yeok (Asian Academy of Management Journal of Accounting and Finance, 2019)
Post global financial crisis central banks worldwide have been crucially concerned about ensuring financial stability in any economy. Malaysia is not an exception where Bank Negara Malaysia has been playing a pivotal role in ensuring continuing safety and soundness of the financial system of the country. In the present paper, we assess the stability of domestic banks in the country using the Distance to Default (DTD). No such analytical study on Malaysian banking has so far been reported in the literature. Using the data of the financial performance of banks during the period 2001 to 2014, their stock price information on daily basis and the corresponding KLCI index, and the daily yield of Malaysian Government Securities, we compute and analyse the DTD of banks at the individual level and also assess the contribution of individual banks to systemic risk. We also assess the robustness of the framework by analysing the cases of two banks which were merged during the period 2001 to 2010. The findings of the study are expected generate extensive research interest in this arena and would also be beneficial to the investor population at large who would be keen in knowing the underpinning of the systemic stability in the country.